2012
DOI: 10.1039/c2jm16554f
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosated biodegradable polymers for biomedical applications: synthesis, characterization and impact of thiol structure on the physicochemical properties

Abstract: A new class of nitric oxide (NO)-releasing biodegradable polymers has been synthesized by derivatizing poly(lactic-co-glycolic-co-hydroxymethyl propionic acid) (PLGH) polymers with structurally unique thiol functionalities followed by nitrosation with t-butyl nitrite to yield pendant S-nitrosothiol moieties. The extent of thiolation was found to be dependent on the thiol moiety itself with the efficiency of incorporation as follows: cysteamine > cysteine > homocysteine. Glutathione and penicillamine were not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 55 publications
1
41
0
2
Order By: Relevance
“…The synthesis of the S -nitrosothiol donor was confirmed using UV-VIS, where the wavelength of maximum absorbance at 340 nm matches that of the characteristic SNO group of other well characterized S -nitrosothiol donors (Figure 2) [46,47,52]. The UV-VIs spectrum of unbound S -nitroso-penicillamine lacks contributions from excess nitrite and nitrous acid from the synthesis step and, thus, could be utilized in further reactions and NO release assays [53].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of the S -nitrosothiol donor was confirmed using UV-VIS, where the wavelength of maximum absorbance at 340 nm matches that of the characteristic SNO group of other well characterized S -nitrosothiol donors (Figure 2) [46,47,52]. The UV-VIs spectrum of unbound S -nitroso-penicillamine lacks contributions from excess nitrite and nitrous acid from the synthesis step and, thus, could be utilized in further reactions and NO release assays [53].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, endothelium is one of the most thromboresisitive materials. Consequently, materials that can release NO at a steady-state equivalent to that released by the natural endothelium (0.5 × 10 −10 mol cm −2 min −1 ) [ 15 ], can be a suitable material for making biomedical devices with enhanced antifouling capabilities [ 16 , 17 ]. Liu et al recently demonstrated that the presence of NO significantly reduces the formation of Shewanella woodyi ( S. woodyi ) biofilm by simultaneously down-regulating the cyclase activity and up-regulating the phosphodiesterase activity of the diguanylate cyclase gene ( Sw DGC) (Fig.…”
Section: Strategies For Making Antifouling Biomedical Surfacesmentioning
confidence: 99%
“…Both are naturally occurring substances in the human body and do not affect normal cell function 67. A new class of biodegradable polymer for NO release has been used for incorporation of RSNOs in to poly(lactic‐ co ‐glycolic‐ co ‐hydroxymethyl propionic acid) (PLGH) 68. Depending on the type of –SH moieties pendant to the polymer backbone, the amounts of NO donor (0.17 and 0.53 mmol SNO g −1 polymer) and its release profile (0.033 and 0.241 mmol NO g −1 polymer) can be controlled and sustained over a 48 h period in vitro ( Figure ).…”
Section: No‐releasing Microparticlesmentioning
confidence: 99%
“…For comparison, the lower‐limit NO flux released by natural ECs is indicated by the black dashed line. Adapted with permission 68. Copyright 2012, Royal Society of Chemistry.…”
Section: No‐releasing Microparticlesmentioning
confidence: 99%